Transformational Leadership in the Implementation of Total Quality Management in Islamic Educational Institutions - Kodir, Abdul; Rotim, Rotim (Fitrah: Journal of Islamic Education, 2024)
The achievement of teacher performance does not only depend on the strategy or approach used, but also depends on the leadership model. The principal of SMPIT Al-Multazam applies a transformational leadership model based on total quality management to improve teacher performance. This research analyzes the principal's role in applying transformational leadership in realizing professional teacher performance. This research uses a case study-based qualitative method, with data collection methods of observation, interviews, and documentation studies. The results found that principals' transformational leadership significantly contributes to improving teachers' motivation, parents' involvement and the implementation of systematic evaluation, which overall improves the quality of education in schools. The active involvement of all stakeholders, including parents, also proved important in supporting the learning process. This study recommends that principals continue to encourage professional development for teachers and increase parental involvement in the education process. Thus, the application of total quality management principles based on transformational leadership can be a model for other Islamic education institutions. The implications of this study show that the application of transformational leadership based on total quality management not only improves teacher performance but also creates an environment conducive to holistic learning.